Pengaruh Kualitas Pelayanan dan Persaingan Terhadap Kepuasan Pelanggan Jasa Servis Pada PT. Astra Honda Motor Unaaha - Muh. Wahyuddin MH. (CV. Aksara Global Akademia, 2024)
This research was conducted to determine the impact of service quality and competition on customer service satisfaction in PT. Astra Honda engine Unaaha. The population of this study includes 100 service customers at PT. Astra Honda engine Unaaha. The analysis method used is multiple Linier regression analysis. The results of this research revealed that service quality and competition simultaneously influence customer service satisfaction in PT. Astra Honda Motor Unaaha has a positive and significant impact on customer service satisfaction at PT. Astra Honda Motor Unaaha, while partly the service quality has a positive and significant influence on customer satisfaction with the services at PT. Astra Honda Motor Unaaha and competition have a positive and insignificant impact on customer service satisfaction at PT. Astra Honda engine Unaaha.